2006
DOI: 10.7498/aps.55.4754
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the granule velocity on the dilute-dense flow transition in granular system

Abstract: The effect of granule velocity on the dilute-dense flow transition in granular system is studied both experimentally and by numerical simulations. Our experiments show that high granule velocity above the exit results in a decrease of critical exit size in dilute-dense flow transition if the inflow rate is fixed. When the granular flow becomes the dense flow, the effect of the granule velocity is counteracted by a high density region above the exit, and the outflow rate is almost irrelative with the granule ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In the granular flow, the two granular states exhibit as two different flow states; i.e., dilute flow state and dense flow state. [8βˆ’10] In a previous study, [8] we have investigated the granular flow in a channel with a specific bottleneck by both experiments and simulations. We found that there is a crucial relationship between the local flow rate and the local packing fraction in a selected choke area under the fixed particle number condition, which can define the granular flow state clearly.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In the granular flow, the two granular states exhibit as two different flow states; i.e., dilute flow state and dense flow state. [8βˆ’10] In a previous study, [8] we have investigated the granular flow in a channel with a specific bottleneck by both experiments and simulations. We found that there is a crucial relationship between the local flow rate and the local packing fraction in a selected choke area under the fixed particle number condition, which can define the granular flow state clearly.…”
mentioning
confidence: 99%
“…To take into account all kinds of granular flow state (including the dense flow state), a soft sphere approach is used to simulate the collision between granules. The detailed interactions form between granules or side wall are the same as those we used in the previous work, [8,13] but in addition to the gravity and the collision between granules or side wall, a normal distributed random force (𝑓 ) is considered to apply to each granules at every time step βˆ†π‘‘. The average of this normal distributed random force is zero in both π‘₯ and 𝑦 directions ( fπ‘₯ = f𝑦 = 0), and the standard deviation is 𝐹 r .…”
mentioning
confidence: 99%
See 3 more Smart Citations